The Role of In Vitro Cultute Methods of Cammelia sinensis L. Plants in the Global Society Transformation - Sutini; Widiwuriani; Guniarti; Agus Purwanto (Future Science)
The purpose of this paper is to explore the role of Cammelia sinensis L in vitro culture in the transformation of a global society with all its changes, both in positive terms and weaknesses. What makes this study relevant to this goal is the transformation of the global society, besides obtaining benefits, it also raises various problems. Problems that arise include the explosion of the world population due to climate change, the threat of malnutrition, the emergence of obesity disorders, disruption of agricultural production and chaos or the high cost of transportation whether by land, sea, or air. The method used is examining the literature on the role of in vitro culture in global social transformation related to climate change, health, agriculture, and transportation. The results obtained from the study of the role of in vitro culture in this global society transformation include obtaining some seeds with certain clones that are resistant to climate change so that nutritional deficiencies can be anticipated, secondary metabolites obtained from Cammelia sinensis L can be applied to reduce obesity. And in vitro culture can facilitate transportation because of the packaging form model from practical-efficient. This study concludes that the in vitro culture method of Cammelia sinensis L is very important in reducing problems in the global society transformation.